Differential effects of type and quantity of leaf damage on growth, reproduction and defence of lima bean (Phaseolus lunatus L.). (30th December 2014) - Blue, E.; Kay, J.; Younginger, B.S.; Ballhorn, D. J.; Leiss, K.
Abstract Folivores are major plant antagonists in most terrestrial ecosystems. However, the quantitative effects of leaf area loss on multiple interacting plant traits are still little understood. We sought to contribute to filling this lack of understanding by applying different types of leaf area removal (complete leaflets versus leaflet parts) and degrees of leaf damage (0, 33 and 66%) to lima bean (Phaseolus lunatus) plants. We quantified various growth and fitness parameters including above‐ and belowground biomass as well as the production of reproductive structures (fruits, seeds). In addition, we measured plant cyanogenic potential (HCNp; direct chemical defence) and production of extrafloral nectar (EFN; indirect defence). Leaf damage reduced above‐ and belowground biomass production in general, but neither variation in quantity nor type of damage resulted in different biomass. Similarly, the number of fruits and seeds was significantly reduced in all damaged plants without significant differences between treatment groups. Seed mass, however, was affected by both type and quantity of leaf damage. Leaf area loss had no impact on HCNp, whereas production of EFN decreased with increasing damage. While EFN production was quantitatively affected by leaf area removal, the type of damage had no effect. Our study provides a thorough analysis of the quantitative and qualitative effects of defoliation on multiple productivity‐related and defensive plant traits and shows strong differences in plant response depending on trait. Quantifying such plant responses is vital to our understanding of the impact of herbivory on plant fitness and productivity in natural and agricultural ecosystems.